Chemerin and PEDF Are Metaflammation-Related Biomarkers of Disease Activity and Obesity in Rheumatoid Arthritis - Tolusso, Barbara; Gigante, Maria Rita; Alivernini, Stefano; Petricca, Luca; Fedele, Anna Laura; Di Mario, Clara; Aquilanti, Barbara; Magurano, Maria Rosaria; Ferraccioli, Gianfranco; Gremese, Elisa (Frontiers in Medicine, 2018)
Objective. Obesity is a risk factor for Rheumatoid Arthritis (RA) being associated to low grade inflammation. This study aimed to determine whether PEDF and Chemerin are biomarkers of inflammation related to fat accumulation in RA and to investigate whether weight loss associates with clinical disease improvement through the modification of fat-related biomarkers in overweight/obese RA with low-moderate disease. Participants and Methods. Two-hundred and thirty RA patients were enrolled, of whom 176 at disease onset treated according to a treat-to-target strategy (T2T) and 54 overweight/obese RA in stable therapy and low-moderate disease activity. Gene expression of adipokines, interleukin-6 and their receptors were examined in adipose tissue from obese RA. Obese RA with low-moderate disease activity underwent low-calories diet aiming to Body Mass Index (BMI) reduction >5%, maintaining RA therapy unchanged. Chemerin, PEDF and Interleukin-6 plasma values were assessed by ELISA and disease activity was evaluated. Results. At RA onset, PEDF and Chemerin plasma values correlated with BMI (p<0.001) but only Chemerin plasma values correlated with disease activity (p<0.001). After adopting a T2T strategy, Chemerin arose as an independent factor associated with remission in early RA [OR(95%CIs):0.49(0.25-0.97)]. Moreover, after low-calories diet, RA with low-moderate disease activity reaching BMI reduction ≥5% (62.6%) at 6 months had significant decrease of PEDF (p<0.05) and Chemerin (p<0.05) plasma values, in parallel with the improvement in disease activity. Conclusions. PEDF and Chemerin arose as biomarkers of obesity and metaflammation respectively, providing a link between chronic inflammation and excess of body weight in RA. Therefore, BMI reduction of at least 5% in obese RA allowed better disease control without modifying RA treatment.